Needs Analysis for the Development of Blended Learning Media Based on PBL to Improve Critical Thinking Skills - Aprilia, Nadia; Syahril, Syahril; Azhar, Azhar (Jurnal Paedagogy, 2024)
This study aims to analyze the requirements for blended learning based PBL learning materials to enhance students’ critical thinking skills when solving physics learning challenges, particularly those about rotational dynamics and equilibrium. This research was survey research as a first step in developing blended learning media based on PBL. The subjects used in this study were junior high school students with a total sample of 105 students and five physics teachers in Pekanbaru and Kampar Regency. The research instrument used in this research was a closed questionnaire developed based on indicators of critical thinking skills and the distribution of critical thinking ability tests. The questionnaire response scores were analyzed using a quantitative descriptive analysis method. The research results showed that learning media was needed to support online and offline learning. The learning media must contain learning materials, videos, and student activities to increase learning effectiveness and train students’ critical thinking skills. Therefore, it is necessary to develop PBL-based blended learning media to improve the critical thinking skills of students and teachers.